Implementation of AICAR analysis by GC‐C‐IRMS for anti‐doping purposes. Issue 11 (17th November 2017) - Buisson, C.; Frelat, C.; Mongongu, C.; Martinat, N.; Audran, M.
Abstract : AICAR (5‐aminoimidazole‐4‐carboxamide‐1‐β‐D‐ribofuranoside), is a naturally occurring substance which is part to the World Anti‐Doping Agency (WADA) Prohibited List. It is claimed to improve physical performance when administered as a supplement. As for other endogenous compounds such as steroids, the gas chromatography‐combustion‐isotope ratio mass spectrometry (GC‐C‐IRMS) analysis remains an efficient tool to differentiate endogenous substances from exogenous ones. A protocol was described in the literature for the analysis of AICAR by GC‐C‐IRMS. The aim of the present study was to implement this protocol in our laboratory and to propose solutions to avoid the difficulties encountered. The first point discussed in this study is the derivatization step. Due to the structure of the AICAR molecule, conventional derivatization for GC‐C‐IRMS such as acetylation could not be applied and silylation was preferred. The improvement of the derivatives stability was achieved thanks to several derivatization conditions tested. This adjustment led to a reproducible derivatization pattern with the 3‐TMS form as major derivative product. The second point discussed in this study is the diminution of extracts' background noise. Indeed, the implementation of the published protocol was not easy due to high performance liquid chromatography (HPLC) problems encountered when concentrated urine was injected into our system. Also, too many interferences in the endogenous reference compound fractions were observed. The addition of both a wash step before the HPLC purification and a HPLC purification step for the endogenous reference compound (ERC) fraction allowed us to increase the robustness of the method. This study presents the modified protocol compared to the original protocol as well as the evaluation of the whole method performances. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The GC‐C‐IRMS analysis of AICAR, a naturally occurring AMKP activator prohibited analogue, was implemented by adjustment with regard to a published protocol. The derivatization step as well as an additional purification step were optimized. The performances of this new protocol were assessed thanks to the repeated analysis of reference material and spiked urine samples. Variability of the  13 C values comparable to the published protocol were obtained with a good reproducibility of the TMS‐derivatives formation.